BUILDING HISTORICAL AWARENESS THROUGH AUDIOVISUAL MEDIA: A STUDY ON THE FILM KADET 1947 BY RAHABI MANDRA AND ALDO SWASTIA - Sawitri, Isma; Saliman, Saliman; Setiawan, Rizky (JURNAL EDUSCIENCE, 2025)
Purpose-This study aims to investigates the effectiveness of audiovisual media, specifically the Indonesian historical film Kadet 1947, in enhancing students’ historical awareness in a vocational education setting.Methodology-The research employed a sequential explanatory mixed-methods design, involving 47 students. Data collection was carried out first with Quantitative data using an instrument in the form of a historical awareness questionnaire, followed by qualitative data from classroom observations and in-depth interviews with selected students. Quantitative data analysis included tests of normality, homogeneity, and paired sample t-tests. Qualitative data were analyzed using Miles and Huberman's (1994) model through the stages of data collection, data reduction, data display, and conclusion drawing.Findings- The study result based on a Quantitative analysis using paired sample t-tests showed a significant increase in historical awareness in the experimental group (p = 0.000< 0,05). In contrast, no significant change was observed in the control group (p = 0.457> 0.05). These results were supported by qualitative findings, which revealed emotional engagement, reflective thinking, identity formation, and increased appreciation for historical artifacts and heritage preservation. The study concludes that Kadet 1947 effectively improves students' historical awareness by reinforcing cognitive understanding and emotional connection to history. This implies integrating local historical films into vocational education to build national identity and promote culturally relevant, pedagogically effective learning.Contribution-The study contributes to history education by offering a media-integrated, context-based instructional approach that supports critical historical awareness and media literacy aligned with students' academic and professional identities.